Train aerodynamics : fundamentals and applications - Baker, Chris (Butterworth-Heinemann, 2019)
Train Aerodynamics: Fundamentals and Applications is the first reference to provide a comprehensive overview of train aerodynamics with full scale data results. With the most up-to-date information on recent advances and the possibilities of improvement in railway facilities, this book will benefit railway engineers, train operators, train manufacturers, infrastructure managers and researchers of train aerodynamics. As the subject of train aerodynamics has evolved slowly over the last few decades with train speeds gradually increasing, and as a result of increasing interest in new train types and high-speed lines, this book provides a timely resource on the topic.